5PSQ-048 What do oncologists and pharmacists think and want from a CAHMs-drug interaction checker? A broadscale survey to assess expectations. Issue 1 (23rd March 2023) - Lammens, A; Neefs, J; Simons, E; Spriet, I; Delforge, M; Janssens, A; Van Nieuwenhuyse, T
Abstract : Background and Importance: The use of complementary and alternative herbal medicines (CAHMs) is widespread and popular among cancer patients for different reasons. Unfortunately, CAHMs can interfere with anticancer treatments leading to both toxicity or decreased efficacy with therapeutic failure. The availability of a tool for the management of potential CAHM-drug interactions (CAHMDI) could provide health care professionals (HCP) with scientific evidence-based information. It may facilitate open communication about potential adverse effects without neglecting patient's beliefs and preferences. Such a tool does not yet exist in our hospital. Aim and Objectives: The aim of this survey was to assess future user's expectations of a practical tool to manage CAHMDI. Material and Methods: Two e-surveys, carried out in Google Forms, were sent to 1) health care providers (HCPs) of all oncological disciplines in our hospital and research departments and 2) all hospital pharmacists of UHL. Results: The survey was completed by 37 HCP and 27 hospital pharmacists (HP). The results clearly demonstrated an interest in a CAHMDI, as confirmed by 94.6% and 100.0% of the HCP and HP, respectively. All respondents indicated a preference for a website rather than a tool integrated in the clinical decision support system (51.0% HCP and 46.4% HP, respectively). In their current daily practice, the most commonly consulted resources for checking CAHMDI by HCP were consulting a clinical pharmacist (33.9%) and Lexicomp Drug Interactions ® (21.4%). HP mentioned Stockley's Herbal Drug Interactions ® (21.3%) and Lexicomp Drug Interactions ® (21.3%). Key requirements for the development of a tool were management options, potential clinical consequences, severity level, mechanism and level of evidence. Conclusion and Relevance: Developing a user-friendly CAHMDI checker would be helpful for HCP and HP. Alerting about HDI could enhance prescribers' knowledge and awareness about this topic and enable them to inform patients about the potential adverse effects of these easily accessible CAHMs. References and/or Acknowledgements: Conflict of Interest: No conflict of interest.